Pengaruh Perkembangan Keuangan Syariah, Investasi Langsung dan Perdagangan Internasional Terhadap Kualitas Udara Di Indonesia - Ahmad Fatoni (ITB AAS INDONESIA Surakarta, 2021)
This study aims to analyze the influence of the development of Islamic finance, direct investment, and international trade on air quality in Indonesia. This research is a quantitative research using panel data. The type of data used is secondary data from 33 provinces in Indonesia from 2017 to 2019. This study uses the Random Effect Model as the best estimation model. The results showed that the variables of Islamic banking financing, domestic direct investment, and international trade (export-import) had a negative and significant effect on air quality in Indonesia. The results of this study prove the hypothesis of the pollution haven effect and the scale effect in Indonesia.